Pemisahan Senyawa 1,4-terpineol dan Safrol dari Minyak Atsiri Biji Pala (Myristica Fragrans Houtt) dan Uji Aktivitas Antibakteri Terhadap Shigella dysenteriae - Tiara Dwi Ayunani; Ines Tri Hastuti; Hery Muhamad Ansory; Anita Nilawati (Fakultas Farmasi Universitas Setia Budi, 2018)
Nutmeg were plants that used as material in food, medicine, perfume and cosmeticsindustries. Nutmeg essential oil contain 1,4-terpineol and safrol compounds that predected haveantibacterial activity.Sparation of 1,4-terpineol and safrol compound from nutmeg essential oil was carried outby fractional distillation method at 95 mmHg and 200- 225C֯. Analysis of nutmeg essential oil andsparation carried out by GC-MS and antibacterial activity tests with diffusion and dilution methods.The Analysis results showed that nutmeg seed essential oil contain 5 mayor compounds,α-pinena, sabinen, 2-β-pinen, terpineol and miristisin, the sparation result contain 40.05%1-4 and20.34% safrol. The diffusion test showed that 1.25% nutmeg seed essential oil have 12,11mminhibition zone that classified as strong inhibition, and the sparation result have 9,66mm inhibitorzone that classified as moderately inhibition. The dilution test result of nutmeg essential oil andthe separation result have activity for bactericidal has the same at consentration 1.25%.